ANALISIS PERBANDINGAN TEBAL PERKERASAN LENTUR METODE ANALISA KOMPONEN BINA MARGA DENGAN METODE DESAIN PERKERASAN JALAN MDPJ 2017 ( STUDI KASUS : JALAN KURAI MUDIAK LIKI SULIKI ) - Maylana Agustin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Road infrastructure development has an important role as a supporter of social and economic activities in the community. However, there are still areas in West Sumatra, one of which is on Road Kurai Mudiak Liki, 50 Regency. Road Kurai is a connecting road between villages in the 50 Regency District which is still in the form of land and has a narrow width. In an effort to improve the condition of the Kurai road, it is necessary to plan for the highway by taking into account the vehicle load, weather, pavement material and soil carrying capacity. The bearing capacity of the subgrade is determined by the value of the California Bearing Ratio which greatly determines the thickness of the pavement layer because it will become the flexible pavement foundation that will be planned. Meanwhile, vehicular traffic, vehicle dimensions and payload will cause a compressive force on the vehicle axle which is supported on the road pavement which is channeled to the subgrade which is also an important reference in determining the thickness of the pavement. This study aims to determine the planning of flexible pavement thickness using the SKBI component analysis method 2.3.26.1987 and the 2017 Road Pavement Design Method No. 02/M/BM/2017 on Road Kurai Mudiak Liki Suliki. To find out which method is stronger for traffic load. The higher the traffic load, the thickness of each layer is important. Based on the calculation results of the two methods, the results obtained in the Component Analysis Method, namely Laston = 11.25 cm, Upper Foundation Layer = 15cm, Lower Foundation Layer = 20cm, and Road Pavement Design Method 2017 obtained calculation results AC-WC = 4 cm, AC-BC4 =6cm, AC-BC or AC Base =7.5cm, CTB3=15cm, Class A Aggregate Foundation=15cm.Keywords: Component Analysis Method, Road Pavement Design Method 2017, Road Kurai Mudiak Liki Suliki